Pneumococcal responses are similar in Papua New Guinean children aged 3-5 years vaccinated in infancy with pneumococcal polysaccharide vaccine with or without prior pneumococcal conjugate vaccine, or without pneumococcal vaccination. - Anita H J van den Biggelaar; Peter C Richmond; Angela Fuery; Denise Anderson; Christine Opa; Gerard Saleu; Mildred Lai; Jacinta P Francis; Michael P Alpers; William S Pomat; Deborah Lehmann (PLoS ONE, 2017)
In an earlier trial, Papua New Guinean (PNG) children at high risk of pneumococcal disease were randomized to receive 0 or 3 doses of 7-valent pneumococcal conjugate vaccine (PCV7), followed by a single dose of 23-valent pneumococcal polysaccharide vaccine (PPV23) at 9 months of age. We here studied in a non-randomized follow-up trial the persistence of pneumococcal immunity in these children at 3-5 years of age (n = 132), and in 121 community controls of a similar age with no prior pneumococcal vaccination.Circulating IgG antibody titers to all PCV7 and PPV23-only serotypes 2, 5 and 7F were measured before and after challenge with 1/5th of a normal PPV23 dose. Serotype-specific memory B-cells were enumerated at 10 months and 3-5 years of age for a subgroup of study children.Serotype-specific IgG antibody titers before and after challenge were similar for children who received PCV7/PPV23, PPV23 only, or no pneumococcal vaccines. Before challenge, at least 89% and 59% of children in all groups had serotype-specific titers ≥ 0.35μg/ml and ≥ 1.0 μg/ml, respectively. Post-challenge antibody titers were higher or similar to pre-challenge titers for most children independent of pneumococcal vaccination history. The rise in antibody titers was significantly lower when pre-challenge titers were higher. Overall the relative number of serotype-specific memory B-cells remained the same or increased between 10 months and 3-5 years of age, and there were no differences in serotype-specific memory B-cell numbers at 3-5 years of age between the three groups.Immunity induced by PCV7 and/or PPV23 immunization in infancy does not exceed that of naturally acquired immunity in 3-5-year-old children living in a highly endemic area. Also, there was no evidence that PPV23 immunization in the first year of life following PCV7 priming induces longer-term hypo-responsiveness.Clinicaltrials.gov NCT01414504 and NCT00219401.